Laparoscopic Repair of Inguinal Hernias - Carter, Jonathan (Springer-Verlag, 2011)
For patients with recurrent inguinal hernia, or bilateral inguinal hernia, or for women, laparoscopic repair offers significant advantages over open techniques with regard to recurrence risk, pain, and recovery. For unilateral first-time hernias, either laparoscopic or open repair with mesh can offer excellent results. The major drawback of laparoscopy is that the technique requires a significant number of cases to master. For surgeons in group practice, it makes sense to have one surgeon in the group perform laparoscopic repairs so that experience can be concentrated. For others, the best technique remains the approach that the surgeon is most comfortable and experienced performing.